2011
DOI: 10.3855/jidc.2078
|View full text |Cite
|
Sign up to set email alerts
|

First report of acute autochthonous hepatitis E in Portugal

Abstract: Hepatitis E infection is usually a self-limiting disease. In industrialized countries, sporadic cases of acute hepatitis E virus (HEV) infections have been described; their number seems to be increasing in European countries. We report the first human case of autochthonous acute hepatitis E confirmed in Portugal. Patients with acute non-A-C hepatitis should be tested for HEV in Portugal and hepatitis E infection should be considered in the differential diagnosis of unexplained hepatitis cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…Further studies are necessary to better understand whether HEV seroprevalence both in human and in pigs is comparable with the current situation on HEV genotype 3 circulation worldwide but with the results presented in this study, it is clear that HEV is highly circulating in fact the first HEV autochthonous case has just been reported by Duque et al. (2012) in Portugal.…”
Section: Discussionsupporting
confidence: 68%
“…Further studies are necessary to better understand whether HEV seroprevalence both in human and in pigs is comparable with the current situation on HEV genotype 3 circulation worldwide but with the results presented in this study, it is clear that HEV is highly circulating in fact the first HEV autochthonous case has just been reported by Duque et al. (2012) in Portugal.…”
Section: Discussionsupporting
confidence: 68%
“…In 1998 in Portugal, Duque et al carried out the first serological study to assess the presence of anti-HEV IgG in 50 blood donors and the results showed that 4% (2/50) were anti-HEV IgG positive [ 105 ]. In this country, the first cases of acute autochthonous hepatitis E virus in humans were described in 2010 [ 106 ].…”
Section: Seroprevalence In the General Population And Risk Groups mentioning
confidence: 99%
“…HEV RNA was also detected at each of three sites (production, processing, and point of sale) in the pork food supply chain. An autochthonous HEV infection was recently described in Portugal in a patient who recalled eating traditional homemade pork sausages made of raw meat about 2 weeks prior to the development of the clinical manifestations of acute hepatitis (Duque et al, 2012). Renou et al (2014) presented the case of the direct evidence of foodborne transmission of HEV after consumption of uncooked "figatellu" sausage in France, with 100% identity between the sequences from the patient and the food product.…”
Section: Viruses In Food-viruses In Fresh Foodmentioning
confidence: 99%